Cardiovascular Effects of an L/N-type Ca2+ Channel Blocker Cilnidipine Assessed in the Chronic Atrioventricular Conduction Block Dogs - Akira Takahara; Atsushi Sugiyama; Yoshioki Satoh; Yuji Nakamura; Keitaro Hashimoto (Elsevier, 2004)
Cardiovascular effects of cilnidipine, a dual L/N-type Ca2+ channel blocker, were evaluated in the chronic atrioventricular block dogs, of which systemic blood pressure and plasma catecholamine levels significantly increased in the pre-drug control. Administration of antihypertensive doses of cilnidipine (1 and 3 μg/kg, i.v.) significantly decreased the total peripheral vascular resistance, mean blood pressure, and atrial rate and increased the cardiac output. These results suggest that cilnidipine not only decreases the blood pressure, but also decreases the sinus automaticity in the in vivo hypertensive condition with increased adrenergic tones. Keywords:: cilnidipine, chronic AV block dog, sympathetic nerve activity